Development of an SPE- HPLC-DAD method for the experimental study of florfenicol and florfenicol amine in pig cerebrospinal fluid - Šandor, Ksenija (Array, 2020)
A study of florfenicol (FF) and its metabo- lite florfenicol amine (FFA) in pig cerebrospinal fluid was conducted following repeated intramuscular administration of the original (reference) and a generic veterinary medicinal product (VMP) under the same experimental conditions (20 mg FF/kg body weight, 48-hour interval). Both VMPs are solutions for injection containing FF as an active substance in the concentration of 300 mg/mL and have been authorized in Croatia for use in cattle and pigs. In this study, clinically healthy pigs were randomly divided into three groups. The first group was treated with the reference VMP, the second with the generic VMP, while the third served as the control group. Animals were sacrificed at 216, 288 and 384 hours after the first drug administration. Cerebrospinal fluid samples were analysed by the optimized and validated high-performance liquid chromatography-diode array detector method (HPLC-DAD). The solid-phase extraction (SPE) technique was chosen for sample preparation. The HPLC-DAD method provides good linearity over the concentration range of 0.05 to 5.00 μg/mL for FF and FFA. Limits of detection were 0.0023 μg/mL for FF and 0.0100 μg/mL for FFA. Extraction recoveries of FF were from 86.6% to 111.8%, and of FFA from 91.7% to 98.8%. The SPE-HPLC-DAD method has been demonstrated to be a selective, sensitive and suitable analytical method for the determination of FF and FFA in cerebrospinal fluid. The present study was based on a preliminary study that quantified FF in pig plasma at 216 hours after the first application of reference or generic VMP. However, FF and FFA were not detected in any of the cerebrospinal fluid samples during the experimental period. According to the nature of biological fluids, the SPE-HPLC-DAD method can be suitable for further pharmacokinetic studies of FF in pig plasma and serum after intramuscular administration of VMPs.